PERUBAHAN LATENSI AMPLITUDO GELOMBANG P100 DAN RECOVERY TIME PADA PASIEN DIABETES MELITUS TIPE 2 TANPA RETINOPATI - Maysam Irawati*, Eva Dewati*, Fitri Octaviana* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION COMPLICATION OF DIABETES MELLITUS IN VISUAL SYSTEM RESULTED TO MACULA AND OPTIC NERVE DYSFUNCTION THE MOST FREQUENT STUDY BEING USED TO ANALYZE MACULA AND OPTIC NERVE WAS VISUAL EVOKED POTENTIAL VEP AND PHOTOSTRESS TEST